Toxicity of entomopathogenic fungi against Spodoptera frugiperda larvae under laboratory conditions - Muhammad Ayaz Shahzad; Muhammad Irfan; Ahmad Abdul Wahab; Farhan Zafar; Abdulrehman; Muhammad Shuban; Muhammad Raheel Saleem (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Maize Fall Armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae) is considered an economically important pest and becoming the main threat to food security. This polyphagous pest is widely distributed in various countries of the world especially tropical and subtropical regions. The toxicity of two entomopathogenic fungi such as Metarhizium anisopliae and Beauveria bassiana were evaluated against 2nd instar larvae of FAW under controlled conditions. The results showed that among tested entomopathogenic fungi, B. bassiana was found more toxic than M. anisopliae. B. bassiana caused 79% larval mortality while M. anisopliae 59%. M. anisopliae and B. bassiana were showed LT50 of 84.01 h and 80.99 h, respectively. M. anisopliae and B. bassiana were showed LC50 of 1.3×107 and 1.8×107 spores ml−1, respectively. The current study concluded that Entomopathogenic fungi can give effective control against early instar and further studies are needed to check the efficacy against older instars under field and laboratory conditions.